KEBIJAKAN PEMERINTAH TENTANG PELAYANAN KEBERSIHAN DI KOTA TANJUNG BALAI KARIMUN TAHUN 2011 - 2013 - Mohamad Rihandra Adiarta; Erman " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Until now, the problem of garbage in Tanjung Balai Karimun still not resolved optimally. This study aims to determine how the role of Local Government in the creation and establishment of local regulations on hygiene services in Karimun. This study used a qualitative method and conducted in Tanjung Balai Karimun.This study uses informants as sources of information objects that aims to achieve mastery in getting information. Data used in this study are primary data and secondary data obtained through direct observation and interviews with informants. Analysis of the data in a descriptive study conducted by describing the data in a systematic and objective so as to produce factual information, current, and accurate.Based on the results of the study found that in general the role of the Department of Health and Landscaping in terms of addressing the waste problem is in accordance with the applicable rules and regulations. However, there are several causes not optimal policy for the purpose of cleanliness and beauty of this city is due to the level of public awareness and legal compliance to environmental hygiene is still low. Although there dissemination of hygiene control and beauty of the city conducted by the Regional Government of Karimun but people are less aware of the importance of cleanliness and beauty of the surroundings. The absence of strict enforcement by the authorities in terms of waste disposal.Keyword: Policies, Health, Tanjung Balai Karimun